Numerical simulation of forced convection heat transfer of laminar cuo-water nanofluid flow through a horizontal 180 degree curve pipe / Hamed Khajeh Arzani - Hamed, Khajeh Arzani (2012)
A fluid formed by suspending Nano-scaled metallic or non-metallic particles in base fluids is called a nanofluid. Laminar forced convection heat transfer of the CUO-water nanofluid in a pipe with a return bend is analysed by using a finite volume method. The effects of nanoparticles concentrations and Reynolds number are investigated on the flow and the convective heat transfer behaviour. The results show that the average Nusselt number increases with increasing Reynolds number, and the increment of specific heat in the nanofluid contributes to the heat transfer enhancement. The average Nusselt number in the return bend appears higher than that in the inlet and outlet pipes due to the secondary flows. However, the pressure drop in the pipe largely increases with the increment of nanoparticle volume concentration.